The Role of International Normalized Ratio (INR) in Heart Failure Patient With Sepsis: Hidden in Plain Sight - Sakti, Pradhika Perdana (Eduvest - Journal of Universal Studies, 2024)
Heart failure is a clinical syndrome characterized by symptoms and signs caused by a structural and/or functional impairment of the heart. Sepsis in heart failure may cause significant mortality and morbidity rates. Clinically, the presence of heart dysfunction in heart failure worsens outcomes in unstable hemodynamic conditions, for instance, in cases of sepsis, particularly in patients with HFrEF. This research aims to survey the blend of heart failure and sepsis and current updates regarding using the International Normalized Ratio (INR) to detect sepsis. Information was collected from various sources, and updated literature was compiled into a review article. The presence of heart failure with sepsis is associated with horrible clinical results. If fluid alone is insufficient to restore perfusion, the fundamental structure of sepsis includes strong fluid recovery followed by vasopressor association (and possibly inotropic support). In any case, in patients with heart failure, high-portion fluid boluses and vasoactive experts might deteriorate the condition. Heart failure and sepsis can overlap and lead to hemodynamic disturbances and challenging treatment. Meanwhile, aggressive fluid resuscitation is necessary for sepsis; conventional heart failure management requires reducing fluid intake. The International Normalized Ratio (INR) is one of the coagulation parameters that may help determine sepsis in patients with heart failure, thus improving appropriate diagnosis and treatment.